Artworks as Protest after Rana Plaza Collapse: Frames, Emotions, and Injustices in the Workers’ Rights Movement in Bangladesh (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
This article details the framing of emotions and workplace injustices through creative avenues and the politics of communication by activist artists from all over the world that worked in the aftermath of the Rana Plaza collapse in 2013 at Savar near Dhaka in Bangladesh. Analyzing poems, photographs, and dramatic performances, used during the protests against Rana Plaza owners, factory owners and the government, I argue that such creative works not only frame the injustices against workers but also the reflexive, affective and moral emotions to motivate audiences in resisting such injustices. After the collapse of Rana Plaza, activists framed their protests trying to express their own anguish and incite different kinds of emotions among their audience that will in turn make them active in protest. Although it is impossible to measure the impact of these creative works of art as protest, these art works are from local and international artists and were presented to transnational audiences, which sheds light on the diffusion of the protest around the world.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(2), 2023, pp. 153-174